Pengaruh Model Pembelajaran Scramble terhadap Hasil Belajar IPA Kelas V SDN 2 Selebung Ketangga - Qusyairi, Lalu A. Hery (Lembaga Yasin AlSys, 2022)
This study aims to determine the effect of using the scramble model on science learning outcomes for fifth grade students at SDN 2 Selebung Ketangga Keruak East Lombok for the 2021/2022 academic year. This research used experiment method with true experimental design and this research use program post-test only control design. The population of this study research was all of fifth grade students of SDN 2 Selebung Ketangga . The sample of this research definited by sampling jenuh technique wich was fifts A as a experiment class and fifth B as a control class. The accumulation data of this research used performance study test. The data analysis used t-test both. The result of hypotheses showed that thitung>ttabel was (2,340 > 2,028) wich means Ho rejected and Ha accepted, it can be concluded that the used of scramble model has influence toward the result of study at fifth grade students of SDN 2 Selebung Ketangga Keruak Lombok Timur in academic years 2021/2022 .